Exploring the Challenge of EFL Learning During the COVID-19 Pandemic - Paisal, Paisal; Regina, Regina; Riyanti, Dwi (KnE Social Sciences, 2022)
Learning English as a foreign language is a challenge for learners in Indonesia. Moreover, the COVID-19 pandemic has forced institutions to adopt an online learning approach. The combination of these problems has thus made it more taxing for EFL learners. Accordingly, the current study was conducted to explore the challenges faced by EFL learners during the pandemic. The study used a descriptive research design, and data were collected qualitatively through semi-structured interviews with 20 participants from MTs Darussalam Kubu Raya. The findings indicated that the commonest issues faced by the learners were their inaccessibility to the Internet and the teachers’ inability to guide or properly explain the lessons. Therefore, the researchers of this study recommend education stakeholders to ensure accessibility of the Internet to their pupils and invest in qualified teachers.